Growth Rate Prediction Using Ann in Production Management - (:unkn) unknown (My University, 2008)
Büyüme oranının tahmini ekonomi yönetimi, üretim yönetimi ve bütçe planlama için çok önemlidir. Bu amaçla hem zaman serileri hem de Yapay Zeka Teknikleri kullanılabilir. Bu teknikleri her ikisini de kullanarak böyle bir çalışma bu makale de yapılmıştır. Zaman serisi verisi ile yıllık büyüme oranı öğrenilebilir ve böylece değişkenlerin geçmiş değerleri gelecek değerleri tahmin etmekte kullanılabilir. Bu makalede, yıllık büyüme oranı, bir otoregresiv model (AR) ve bir Yapay Sinir Ağları (ANN) modeli yardımıyla ANN simülatörü kullanılarak gerçekleştirilmiştir. Gelecek yıllarda büyüme oranları , ANN simülatörü ve zaman serisi analizi yardımıyla yukarıda bahsedilen parametrelere bağlı olarak tahmin edilmiştir. Sonra sonuçlar karşılaştırılmıştır. Sonuçlar göstermiştir ki ANN model yardımıyla elde edilen tahmin hatası AR modeli ile elde edilenden daha küçüktür.

The prediction of growth rate is a vital importance for economy management, production planning and budget planning. Both the time series techniques and artificial intelligent techniques can be used for this aim. Such a prediction study using both of these techniques is made in this study. With time series data, the annual growth rate can be learned and therefore past values of variables can be used to predict the future values. In this paper, annual growth rate has been predicted by an autoregressive (AR) model and an artificial neural network (ANN) model implemented by ANN simulator developed by the researcher. Future growth rates have been forecasted depending on the above mentioned parameters via time series analysis and ANN simulator then the results were compared. The results showed that the prediction error obtained by ANN model is smaller than the error obtained by AR model.